2022
DOI: 10.1186/s12882-022-02756-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to hemodialysis and medical regimens among patients with end-stage renal disease during COVID-19 pandemic: a cross-sectional study

Abstract: Background Adherence of patients with End-Stage Renal Disease (ESRD) to Hemodialysis (HD), prescribed medications, diet and fluid restrictions is essential to get the desirable outcome and prevent complications. During COVID-19 pandemic, ESRD patients became more concerned with attending the HD sessions and following the protective measures because of the potential for increased susceptibility to COVID-19. The aim of this study was to evaluate the impact of the pandemic on patients' adherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
3
7
0
1
Order By: Relevance
“…Our study shows that fear of COVID-19 is associated with lower scores of treatment adherence. This finding is in line with a prior study, which found that insufficient knowledge and low perception scores, as well as a high fear of COVID-19, were the primary predictors of non-adherence [ 15 ]. Furthermore, the fear of COVID-19 also increased the chemotherapy postponement rate in cancer patients [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study shows that fear of COVID-19 is associated with lower scores of treatment adherence. This finding is in line with a prior study, which found that insufficient knowledge and low perception scores, as well as a high fear of COVID-19, were the primary predictors of non-adherence [ 15 ]. Furthermore, the fear of COVID-19 also increased the chemotherapy postponement rate in cancer patients [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…The responses ranged from 0 to 200. The overall score ranges from 0 to 1200, with higher scores indicating better TA [ 15 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…En general, 122 (55,5%) pacientes tuvieron una buena adherencia, 89 (40,5%) tuvieron una adherencia moderada y 9 (4,1%) tuvieron un comportamiento de adherencia deficiente 4 . En Egipto, la pandemia de COVID-19 afectó negativamente la adherencia de los pacientes a la HD y al tratamiento farmacológico 5 . En Brasil, evaluaron la adherencia farmacológica en pacientes en HD encontrando que el 62,2% tuvo baja adherencia, mientras que solo el 33,8% mostró una alta adherencia al tratamiento, además mostraron que la disminución de adherencia al tratamiento tenía relación con factores propios de la persona (edad, sexo, y nivel educativo) 6 .…”
Section: Introductionunclassified